The national scenarios for emissions reduction in residential heating sector in Poland - Niemierka Elżbieta; Jadwiszczak Piotr (E3S Web of Conferences, 2017)
Today’s residential heating sector (RHS) in Poland is based mainly on fossil fuels combustion, both in individual and large-scale heat sources. The RHS emissions significantly contribute to the outdoor air quality deterioration, especially by low-stack emissions in the heating season. Following the example of other EU countries, the national scenarios for emissions reduction in RHS are an effective tool for outdoor air quality improvement. The scenarios contain a replacement of the existing heat sources in RHS with heat generation technologies in the scale of the country, like high-efficiency gas boilers, biomass boilers or heat pumps. The study takes into account today’s RHS structure in Poland, the scenarios feasibility and achieved emissions reduction.